Kinase inhibitors developed for treatment of hematologic malignancies: implications for immune modulation in COVID-19 - Jacobs, Chaja F. (Blood Adv, 2021)
Tyrosine kinase inhibitors (TKIs) are used to target dysregulated signaling pathways in virtually all hematologic malignancies. Many of the targeted signaling pathways are also essential in nonmalignant immune cells. The current coronavirus severe acute respiratory syndrome coronavirus 2 pandemic catalyzed clinical exploration of TKIs in the treatment of the various stages of COVID-19, which are characterized by distinct immune-related complications. Most of the reported effects of TKIs on immune regulation have been explored in vitro, with different class-specific drugs having nonoverlapping target affinities. Moreover, many of the reported in vivo effects are based on artificial animal models or on observations made in symptomatic patients with a hematologic malignancy who often already suffer from disturbed immune regulation. Based on in vitro and clinical observations, we attempt to decipher the impact of the main TKIs approved or in late-stage development for the treatment of hematological malignancies, including inhibitors of Bruton’s tyrosine kinase, spleen tyrosine kinase, BCR-Abl, phosphatidylinositol 3-kinase/ mammalian target of rapamycin, JAK/STAT, and FMS-like tyrosine kinase 3, to provide a rationale for how such inhibitors could modify clinical courses of diseases, such as COVID-19.